Answer:
x = -6
Step-by-step explanation:
1. Simplify [tex]\frac{4}{3} x[/tex] to [tex]\frac{4x}{3}[/tex]
[tex]-16=\frac{4x}{3} -8[/tex]
2. Add 8 to both sides
[tex]-16+8=\frac{4x}{3}[/tex]
3. Simplify the right side by adding
[tex]-8=\frac{4x}{3}[/tex]
4. Multiply both sides by three, getting rid of our fraction
[tex]-8*3=4x[/tex]
5. Simplify the right side by multiplying
[tex]-24=4x[/tex]
6. Divide both sides by 4 to remove the 4x
[tex]-\frac{24}{4} =x[/tex]
7. Simplify 24/4 to 6
[tex]-6=x[/tex]
8. Switch the sides of the equation so to be in a proper format
[tex]x=-6[/tex]
Hope I helped! If you don't mind giving brainliest I would really appreciate it!